Induksi Mutasi Kalus Embriogenik Gandum (Triticum aestivum L.) melalui Iradiasi Sinar Gamma untuk Toleransi Suhu Tinggi - Setiawan, Ryan Budi; Khumaida, Nurul; Dinarti, Diny (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
Mutation techniques through gamma ray irradiation is useful to support breeding programs for genetic improvement of wheat. Genetic improvement on tolerance to high temperatures is necessary for development of wheat in Indonesia. The purpose of this study was to determine the level of radiosensitivity to be used as the basis for the induction of mutations by gamma ray irradiation on embryogenic callus to obtain putative mutants with high temperature tolerance. Explants used were embryogenic callus cultured on MS medium containing 30 g L-1 sukrosa, 2 g L-1 gelrite, 2 mg L-1 2.4D and 1 mg L-1 picloram. Culture incubated for 6 weeks with temperature 20±4 oC in the room culture. Five irradiation doses (10, 20, 30, 40 and 50 Gy) were used in radiosensitivity testing. A factorial, completely randomized design was applied to the experiment. The first factor was selection temperature with three levels (25, 30 and 35 oC), and the second factor was doses of gamma ray iradiation with three levels (10, 20, and 30 Gy). The result showed that radiosensitivity levels varied among varieties, LD20: 7.79 to 18.96 Gy and LD50: 24.29-33.63 Gy. Selayar variety which has highest sensitivity value compared with Dewata and Nias. Increasing doses of iradiation and temperature decrease survival of embryogenic callus, number of embryos, and percentage of germinated plantlets. Based on in vitro selection using high temperature (25, 30, and 35 oC), the obtained 19 putative mutants were derived from embryos that appear on the surface of embryogenic callus survival after irradiation and high temperature selection.Keywords: in vitro selection, putative mutant, radiosensitivity, somatic embryo